2015
DOI: 10.1002/cphc.201402629
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Globular Plasma Proteins with Water‐Soluble CdSe Quantum Dots

Abstract: The interactions between water-soluble semiconductor quantum dots [hydrophilic 3-mercaptopropionic acid (MPA)-coated CdSe] and three globular plasma proteins, namely, bovine serum albumin (BSA), β-lactoglobulin (β-Lg) and human serum albumin (HSA), are investigated. Acidic residues of protein molecules form electrostatic interactions with these quantum dots (QDs). To determine the stoichiometry of proteins bound to QDs, we used dynamic light scattering (DLS) and zeta potential techniques. Fluorescence resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Some of these interactions where the macromolecular scaffolds can serve as templates for ultra-small nanoparticles deposition and resulting changes in protein folding (summarised by Shemetov et al [121]), are bound to have profound bilateral effects both of protein and QDs properties. Indeed, Pathak et al more recently studied the interactions between water-soluble MPA-coated semiconductor CdSe QDs and three globular plasma proteins, including bovine serum albumin, b-lactoglobulin and human serum albumin and found that acidic residues of these proteins engaged in electrostatic interactions with QDs and upon binding with QDs, protein molecules underwent substantial conformational changes at the secondary-structure level with up to 50% loss in helicity [122]. Maffre et al investigated the adsorption of human serum albumin onto FeePt nanoparticles, CdSe/ZnS QDs, Au and Ag nanoclusters of 6, 5 and 1e4 nm radii, respectively.…”
Section: Unresolved Problems Challenges and Controversiesmentioning
confidence: 99%
“…Some of these interactions where the macromolecular scaffolds can serve as templates for ultra-small nanoparticles deposition and resulting changes in protein folding (summarised by Shemetov et al [121]), are bound to have profound bilateral effects both of protein and QDs properties. Indeed, Pathak et al more recently studied the interactions between water-soluble MPA-coated semiconductor CdSe QDs and three globular plasma proteins, including bovine serum albumin, b-lactoglobulin and human serum albumin and found that acidic residues of these proteins engaged in electrostatic interactions with QDs and upon binding with QDs, protein molecules underwent substantial conformational changes at the secondary-structure level with up to 50% loss in helicity [122]. Maffre et al investigated the adsorption of human serum albumin onto FeePt nanoparticles, CdSe/ZnS QDs, Au and Ag nanoclusters of 6, 5 and 1e4 nm radii, respectively.…”
Section: Unresolved Problems Challenges and Controversiesmentioning
confidence: 99%
“…As an alternative, researchers choose semiconductor quantum dots (QDs) because of their high quantum yield and low photobleaching characters. Previously studied QDs that exhibit a molecular interaction with proteins consist of toxic heavy metal ions, such as cadmium, lead, selenium, or mercury [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[48] Fluorescence investigation of bioconjugates comprising quantum dots and bovine serum albumin (BSA) has indicated the formation of a protein layer on the quantum dots. [49,50] Dye-quantum dot conjugates have been used for ratiometric sensing of proteins. [51] Literature report on water soluble nanotetrapods is scarce.…”
Section: Introductionmentioning
confidence: 99%